Hubungan Pengetahuan Ibu Hamil Risiko Tinggi Tentang Kehamilan Risiko Tinggi Kabupaten Ciamis Tahun 2015 - Siti Saadah Mardiah (STIKes Persada Husada Indonesia, 2015)
High risk pregnancy is a pregnancy that is expected to occur disruption of out-come to her mother orher fetus to require more intensive supervision and may act proactively. This research aim to detect therelationship between mother high risk pregnant knowledge about high risk pregnancies with antenatal care atcommunity health center District Banjarsari Regency Ciamis 2015. Knowledge or cognitive domain is veryimportant for someone action (over behavior). High risk pregnancy needs monitoring and proactive action. Themethod in this research is an analytic survey with cross-sectional approach. The population in this study is thehigh risk pregnant mothers for being too young, too old, too many and too close to the health center BanjarsariCiamis District during the study (week IV in November and week I in December 2015) by using the totalsampling of 31 people. Primary data (knowledge of mother with high risk pregnancy) were collected throughquestionnaires, secondary data obtained by visiting antenatal form women cohort. Statistical analysis used ChiSquare test. The research showed that knowledge of high-risk pregnant women is categorized quite enough asmany as 14 people (45.2%), antenatal care of high-risk pregnant women accordingto the standard as many as 13people (41,9%). Statistical tests using chi-square analysis with significance level of 0.05, got value 2 as big as10,192 with  value as big as 0,017. The conclusion of this research there is relationship between mother highrisk pregnant knowledge about high-risk pregnant with antenatal care at community health center DistrictBanjarsari Regency Ciamis 2015. It is recommended for pregnant women to do more health activities andperform routine check the pregnancy antenatal care.Keywords: knowledge, pregnancy, antenatal care